1994
DOI: 10.1104/pp.105.1.3
|View full text |Cite
|
Sign up to set email alerts
|

N Demand and the Regulation of Nitrate Uptake

Abstract: Uptake of nitrate by root cells followed by reduction and assimilation in plant tissues is the main route by which mineral N is converted into organic N by living organisms. Like photosynthesis, these are life-dependent processes that members of the animal kingdom are unable to perform for themselves. Nitrate and other mineral nutrients required for optimal plant growth and development frequently exist at relatively low concentrations in soil. To thrive on these dilute nutrients, plants have developed high-per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
242
0
6

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 425 publications
(262 citation statements)
references
References 14 publications
(9 reference statements)
14
242
0
6
Order By: Relevance
“…For example, the evidence that the uptake of inorganic ions by roots is regulated in accordance with the shoot's demand for the ions (Marschner, 1995), has led to a search for the means by which the shoot can communicate its requirements to the transport systems of the root. For N, it has been proposed that the rapid cycling of amino acids which occurs between shoot and root would serve to provide the root with the necessary information about changes in the shoot's N status (Cooper and Clarkson, 1989;Imsande and Touraine, 1994). However, contrary to the requirements of this model it is sometimes found that N deficiency can lead to an increase rather than a decline in amino acid cycling (e.g., Peuke et al, 1994).…”
Section: Systemic Responsesmentioning
confidence: 85%
“…For example, the evidence that the uptake of inorganic ions by roots is regulated in accordance with the shoot's demand for the ions (Marschner, 1995), has led to a search for the means by which the shoot can communicate its requirements to the transport systems of the root. For N, it has been proposed that the rapid cycling of amino acids which occurs between shoot and root would serve to provide the root with the necessary information about changes in the shoot's N status (Cooper and Clarkson, 1989;Imsande and Touraine, 1994). However, contrary to the requirements of this model it is sometimes found that N deficiency can lead to an increase rather than a decline in amino acid cycling (e.g., Peuke et al, 1994).…”
Section: Systemic Responsesmentioning
confidence: 85%
“…Inhibition of nitrate uptake by ammonium is well described in woody species (Serna et al 1992;Kreuzwieser et al 1997;Gessler et al 1998). Some research considered that the products of nitrate and ammonium assimilation resulted in the inhibition, because the products, such as amino acids, were responsible for the down-regulation of nitrate uptake when ammonium is supplied simultaneously (Lee et al 1992;Imsande and Touraine 1994). After uptake, ammonium is assimilated mainly in the roots, while the NO 3 -is assimilated in both roots and shoots of plants (Andrews 1986;Munzarova et al 2006), and the ammonium can be converted into amino acids directly, whereas NO 3 -needs to be reduced to NH 4…”
Section: Sex-specific Difference Of Biomass Accumulation and Allocationmentioning
confidence: 99%
“…Nitrate uptake is thought to be strongly regulated by the N demand of the plant (Imsande & Touraine, 1994). A possible mechanism of control is the transport of products of nitrate reduction, namely carboxylates, from the site of nitrate reduction to that of nitrate uptake.…”
Section: mentioning
confidence: 99%